Benign adult familial myoclonus epilepsy (BAFME): an autosomal dominant form not linked to the dentatorubral pallidoluysian atrophy (DRPLA) gene. Issue 1 (January 1996) - Kuwano, A; Takakubo, F; Morimoto, Y; Uyama, E; Uchino, M; Ando, M; Yasuda, T; Terao, A; Hayama, T; Kobayashi, R; Kondo, I
Abstract : The genetic differences between two types of dominant inherited myoclonus epilepsy, dentatorubral pallidoluysian atrophy (DRPLA) and benign adult familial myoclonus epilepsy (BAFME), have been reported. A gene with a CAG repeat expansion responsible for DRPLA has been isolated. We have examined CAG repeat expansion in the DRPLA gene in five BAFME families, and the abnormal CAG expansion was not observed in the affected subjects. Linkage analysis using DNA polymorphisms in the DRPLA gene and the genes for gamma-aminobutyric acid (GABA) receptor subunits, GABAR beta 1, GABAR beta 3, and GABAR alpha 6, showed that these genes were not responsible for BAFME.